The influence of training design factors on training transfer: a preliminary study - Zulkifly, Nurul Afiqah (Human Resource Management Academic Research Society, 2022)
Organizations invest considerably in training and development programmes anticipating successful outcomes. An unsuccessful training is often associated with poor return on investment. An effective training focuses on two critical components, which are the design of the training, also known as training design factors comprising of perceived content validity and transfer design, as well as training transfer, but few of them focus on the context of academics in university. Thus, this preliminary study aims to expand training and development body of knowledge through the investigation of the relationships and influence of training design factors on training transfer. This quantitative, correlational research uses simple random sampling technique to determine the required sample size. This study involves a total of 100 academics who are working in a public, research university in Malaysia. The academics have previously attended a training programme organized by the university prior to participating in this study. Results show that both training design factors i.e., perceived content validity and transfer design are significantly related to but are not significantly influencing training transfer among the academics. It is highly recommended for future researchers to replicate this study with a bigger sample size and to include other variables related to training transfer as well.